169:poster Gaps in healthcare services leading to high extra-pulmonary tuberculosis un-addressed high economic burden of extra-pulmonary tuberculosis patients. (28th April 2022) - Hassan, Shoaib; Mustafa, Tehmina; Robberstad, Bjarne; Norheim, Ole Frithjof
Abstract : Background: Tuberculosis (TB), annual disease-burden >10.0 million is associated with socioeconomic disparities. Moreover, extrapulmonary tuberculosis (EPTB), despite its high disease-burden, Universal Health Coverage (UHC) implementation remains growing a public health concern. Methods: We conducted a prospective cohort study from August 2014-2015 at Mnazi-Mmoja Hospital, Zanzibar. EPTB patients were interviewed for demographic and socioeconomic information and pre-diagnostic cost of EPTB was ascertained. Finally, regression analysis was used to identify factors predicting the high pre-diagnostic total cost for patients. Results: EPTB patients were predominantly children (35%) and young adults (50%); 55% were male. Average monthly income was US 136 with no significant difference by gender. The median total cost for all patients was US 98, mainly due to average indirect costs (65%). Around 58% of the patients suffered from catastrophic costs. On average, patients faced 67 days of reduced-productivity due to EPTB illness. Increase in average monthly income was the significant predictor of high total patient cost for all and male patients respectively, while increase in reduced working capacity led to a decrease in total cost for the female patients. Discussion: The calculated out-of-pocket and opportunity-costs caused significant socio-economic burden as compared to the developed-countries. Alarmingly, pre-diagnostic costs are linked with patients' ability to pay which highlights potential gaps in available UHC and a significant barrier to end-TB goals. The higher catastrophic-costs pushes the worse-off further into poverty and major barrier to achieve UHC. These findings highlight the need of affordable early interventions to tackle EPTB and avoid inequity by reducing socioeconomic burden.